Interannual spatio-temporal evolution of the supraglacial lakes on the Belvedere Glacier between 2000 and 2023 - Brodský, Lukáš; Rusnák, Samo; Schmidt, Susanne; Vilímek, Vít; Azzoni, Roberto Sergio; Nüsser, Marcus; Tronti, Gianluca; Kropáček, Jan; Pandey, Aayushi (Acta Universitatis Carolinae. Geographica, 2024)
Understanding of the formation and evolution of supraglacial lakes in high mountain regions is crucial for accurately assessing their impact on glacier behaviour, hydrology, and potential hazards such as outburst floods. This article examines the annual spatio-temporal evolution of supraglacial lakes on the Belvedere Glacier between 2000 and 2023. Very high-resolution aerial photography and high-resolution satellite imagery were used to identify supraglacial lakes as small as 37 m2 and narrow bands of ice-marginal lakes. The mapping revealed that the well-known Lake Effimero is stable in its position but unstable in size, with variations from 428 m2 to 99.7 × 103 m2. These changes are potentially due to snowmelt or glacier dynamics. In 2002, the area of Effimero was at its largest extent observed during the study period. The first appearance of the Lake Effimero was revelated by the Landsat imagery on 27 May 2001, which differed from the findings of other studies. New lakes were observed to form in a manner independent of Effimero formation, exhibiting a consistent annual occurrence with nearly linear area growth up to 9.7 × 103 m2 in 2023. The formation of the lakes is shown to be influenced by their morphological characteristics.